2015
DOI: 10.1038/jid.2015.335
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Vitiligo Skin Reveals the Alteration of WNT Pathway: A Promising Target for Repigmenting Vitiligo Patients

Abstract: Vitiligo affects 1% of the worldwide population. Halting disease progression and repigmenting the lesional skin represent the two faces of therapeutic challenge in vitiligo. We performed transcriptome analysis on lesional, perilesional, and non-depigmented skin from vitiligo patients and on matched skin from healthy subjects. We found a significant increase in CXCL10 in non-depigmented and perilesional vitiligo skin compared with levels in healthy control skin; however, neither CXCL10 nor other immune factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
151
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 24 publications
16
151
1
2
Order By: Relevance
“…Transcriptomic analysis of HEM-l and PIG3V revealed similar changes in many of the immune, cell cycle, and pigmentation pathway genes shown to be differentially expressed in vitiliginous lesions (Dey-Rao and Sinha, 2016, Rashighi et al , 2014, Regazzetti et al , 2015). Our finding of highly significant downregulation of pigmentation genes downstream of MITF (a master regulator of melanogenesis, six-fold downregulated) A in PIG3V cells confirmed defects in melanin biosynthesis and pigmentation and provided confidence that the changes seen in vitro were representative of the clinical disease state.…”
Section: Discussionmentioning
confidence: 94%
“…Transcriptomic analysis of HEM-l and PIG3V revealed similar changes in many of the immune, cell cycle, and pigmentation pathway genes shown to be differentially expressed in vitiliginous lesions (Dey-Rao and Sinha, 2016, Rashighi et al , 2014, Regazzetti et al , 2015). Our finding of highly significant downregulation of pigmentation genes downstream of MITF (a master regulator of melanogenesis, six-fold downregulated) A in PIG3V cells confirmed defects in melanin biosynthesis and pigmentation and provided confidence that the changes seen in vitro were representative of the clinical disease state.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study that examined a large number of vitiligo patients, serum levels of CXCL9 and CXCL10 correlated with disease activity, while only CXCL10 reflected disease severity (Wang et al , 2016), and another study reported low-level expression of CXCL10 in stable lesions (Regazzetti et al , 2015). Therefore, targeting both CXCL9 and CXCL10 may be important for treating active disease, whereas stable disease may be treated by blocking CXCL10 alone (Rashighi et al , 2014; Regazzetti et al , 2015; Wang et al , 2016). Future clinical studies will need to be conducted to determine the therapeutic potential for targeting CXCR3 ligand expression in keratinocytes as a treatment for vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…However, in keratinocytes increased apoptosis and oxidative stress have also been found, indicating that the oxidative findings in vitiligo are not melanocyte specific . It is currently unclear whether epidermal oxidative stress is indeed the primary cause leading to the release of proinflammatory chemokines or if a generalized subtle skin inflammation may explain the findings on oxidative stress in non‐lesional vitiligo skin . Evidence for a small‐scale inflammation has indeed been found in non‐lesional vitiligo skin with more expression of chemokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10) and overexpressed innate immune markers (e.g. natural killer cell receptors KLCR4 and KLRG1) in normal‐appearing skin …”
Section: Discussionmentioning
confidence: 99%